Integrasi Teologi dan Ilmu Pengetahuan dan Teknologi (IPTEK): Transformasi Pendidikan Islam Menuju Generasi Emas 2045 - Aisyah, Nagita Histimuna; Kahfi, Nazih Sadatul; Nisa, Siti Ma'rufatun; Shodiq, Shodiq; Mas'ud, Abdurrahman (Universitas Negeri Padang, 2025)
The year 2045 marks the 100th anniversary of Indonesia's independence, which is anticipated to herald the emergence of a golden generation. This golden generation refers to Indonesian individuals who are excellent, accomplished, and competent in various fields of technology and science, contributing to transforming the Republic of Indonesia into a strong, advanced, significant, and sovereign nation on the international stage. However, the globalization era, characterized by rapid technological advancements and the massive flow of information, has created a disruptive environment posing significant challenges, particularly in Islamic education. This study aims to explain the integration of Islamic values through Islamic education to prepare a golden generation that remains resilient in spiritual values and does not lose focus amid advancements in science and technology (STEM). The study employs a library research method with content and descriptive analysis to examine the concept of this integration. The findings indicate that the integration of Islamic theology and STEM serves as a strategic approach to building a golden generation that is morally and intellectually robust. This study emphasizes the critical role of Islamic education as a foundation for shaping an outstanding generation capable of addressing contemporary challenges while maintaining their spiritual identity.